Analysis and modelling of an induction machine with a pulsating load torque used for a washing machine application - Lundström, Linda; Hedin, Magnus (My University, 2007)
The goal of this master thesis is to derive a model of the induction machine that drives the washing machine drum, a model for the drum with an unbalanced load and to derive a controller for the induction machine. In addition to the models, it should also be investigated if the currents, drawn by the induction machine, will vary with the unbalanced load. Finally it should be investigated if it is possible to determine the mass of the unbalanced load simply by looking at the stator currents. A vector control drive consisting of a current and a speed PI-controller have been derived and implemented in MATLAB/Simulink. Two controllers have been derived, one equipped with a flux estimator for speed sensored control and the other with a flux and speed estimator for sensorless control. The induction machine model and the model for the washing drum with unbalanced load have been verified to work as intended. It was also found that it should be possible to measure the currents, represented in the synchronously rotating reference frame, drawn by the induction machine to determine the size of the unbalanced load.
Keywords: Elkraftteknik; Electric power engineering